Emotional Dissonance and Burnout: The Moderating Role of Team Reflexivity and Re‐Evaluation. (19th July 2016) - Andela, Marie; Truchot, Didier
Abstract: The aim of the present study was to better understand the relationship between emotional dissonance and burnout by exploring the buffering effects of re‐evaluation and team reflexivity. The study was conducted with a sample of 445 nurses and healthcare assistants from a general hospital. Team reflexivity was evaluated with the validation of the French version of the team reflexivity scale (Facchin, Tschan, Gurtner, Cohen, & Dupuis, 2006). Burnout was measured with the MBI General Survey (Schaufeli, Leiter, Maslach, & Jackson, 1996). Emotional dissonance and re‐evaluation were measured with the scale developed by Andela, Truchot, & Borteyrou (2015). With reference to Rimé's theoretical model (2009), we suggested that both dimensions of team reflexivity (task and social reflexivity) respond to both psychological necessities induced by dissonance (cognitive clarification and socio‐affective necessities). Firstly, results indicated that emotional dissonance was related to burnout. Secondly, regression analysis confirmed the buffering role of re‐evaluation and social reflexivity on the emotional exhaustion of emotional dissonance. Overall, results contribute to the literature by highlighting the moderating effect of re‐evaluation and team reflexivity in analysing the relationship between emotional dissonance and burnout. Copyright © 2016 John Wiley & Sons, Ltd.